The Correlation Between Age of Marriage and Parity with Women in the Act of doing Pap Smear (Study in Wisnuwardhana Surabaya Cancer Foundation Period January-June 2015) - Ufiyah Hakimah (Universitas Airlangga, 2016)
Cervical cancer is the 2nd leading cause of death for women in Indonesia. This disease can be detected early through pap smears. This research was conducted to analyze the relationship between married age and parity with the actions of women in conducting Pap Smear examinations at the Wisnuwardhana Cancer Foundation, Surabaya. This research uses analytic observational research with a case-control research design. The study was conducted at the Wisnuwardhana Cancer Foundation, Surabaya in 2015. A sample of 96 women of childbearing age couples with a case and control group comparison of 1: 1. The independent variables studied were marriage age and parity, while the dependent variable was the actions of women in carrying out Pap Smear examinations. Data collection techniques using a questionnaire instrument and a checklist of visits at the Wisnuwardhana Cancer Foundation Surabaya This study uses a systematic random sampling technique and uses a chi-square test data analysis technique. The results of the study showed that there is a relationship between married age (p = 0.025; OR = 2.783), parity (p = 0.014; OR = 3.08) with the actions of women in conducting Pap Smear examinations at the Wisnuwardhana Cancer Foundation, Surabaya. It was concluded that women of childbearing age who have married age> 20 years and have two or more children (multipara) have the opportunity to take Pap Smears. Health workers are advised to provide information, especially on risk factors for cervical cancer, so that early detection of cervical cancer can be done, especially for those who have risk factors for cervical cancer.